2020
DOI: 10.4103/ejgd.ejgd_216_19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical workflow of two different CAD/CAM systems for veneers manufacture

Abstract: Digital technology is improving dentistry by manufacturing restorations faster and easier. Veneers can be handcrafted fabricated by the dental technician or designed by software and fabricated by a milling machine. Currently, there are many scanners available in the market that are clinically acceptable for the fabrication of restorations. However, there have been no clinical reports comparing the clinical protocols of the two most frequently used software programs in the market. The aim of this article is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recent studies have demonstrated that CAD–CAM restorations have a better marginal adaptation than conventionally fabricated indirect restorations 8,9 . Similar to CAD–CAM complete coverage restorations, laminate veneers (LVs) can be fabricated using CAD–CAM technology where an intraoral scanner (IOS) is used to register the preparation, designed, and then milled from a material of choice 10,11 . These restorations have been shown to provide high esthetic results to fulfill patient demands 12,13 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that CAD–CAM restorations have a better marginal adaptation than conventionally fabricated indirect restorations 8,9 . Similar to CAD–CAM complete coverage restorations, laminate veneers (LVs) can be fabricated using CAD–CAM technology where an intraoral scanner (IOS) is used to register the preparation, designed, and then milled from a material of choice 10,11 . These restorations have been shown to provide high esthetic results to fulfill patient demands 12,13 .…”
Section: Figurementioning
confidence: 99%
“…8,9 Similar to CAD-CAM complete cov-erage restorations, laminate veneers (LVs) can be fabricated using CAD-CAM technology where an intraoral scanner (IOS) is used to register the preparation, designed, and then milled from a material of choice. 10,11 These restorations have been shown to provide high esthetic results to fulfill patient demands. 12,13 LVs fabricated using digital workflow have shown a satisfactory survival rate of 94% after 9 years.…”
mentioning
confidence: 99%